Political mobilization in East Central Europe. Issue 3 (4th May 2017) - Brunnbauer, Ulf; Haslinger, Peter
Abstract : This article provides an introduction to the special thematic section on political mobilization in East Central Europe. Based on a brief presentation of the main arguments of the individual articles, the authors discuss the recent political volatility in East Central Europe. They highlight the tension between fierce political rhetoric and populist policies on the one hand, and low levels of voter turnout and overall political participation in the region on the other. The authors argue that recent cases of successful as well as unsuccessful political mobilization in East Central Europe point to structural re-alignments in the region's political landscape. In particular, the parties that are successful are those that manage to communicate their visions in new ways and whose messages resonate with nested attitudes and preferences of the electorate. These parties typically rally against the so-called establishment and claim for themselves an anti-hegemonic agenda. The introductory essay also asserts that these developments in East Central Europe deserve attention for their potential Europe-wide repercussions – especially the idea of "illiberal democracy, " which combines populist mobilization and autocratic demobilization and finds adherents also in more established European democracies.